Value creation through lean management: a case study of healthcare service operations. (2016) - Salam, Mohammad Asif; Khan, Sami A.
The purpose of this case study was to analyse a healthcare service facility, Thai Medical Centre (TMC), by applying lean thinking for system-wide process improvement and improved patient satisfaction. To address the research problem, a simulation-based case study was designed based on a private healthcare facility in Thailand. In this research, an attempt was made to understand and evaluate the factors associated with running an efficient healthcare system. Using the lean methodology process and the layout at the centre, the TMC system was analysed and then redesigned to optimise the lead time at its health promotion centre. The findings of this study demonstrate that through adopting lean process the system can become more efficient by providing a better, faster and safer healthcare system, which contributes to patient satisfaction. Also, these findings can be benchmarked elsewhere in order to improve healthcare system-wide efficiency.